2013
DOI: 10.1002/etc.2102
|View full text |Cite
|
Sign up to set email alerts
|

A three‐generational study of In ovo exposure to PBDE‐99 in the zebra finch

Abstract: Abstract-Based on a literature review of avian data for polybrominated diphenyl ethers (PBDEs), ecologically relevant doses, low (10 ng/egg), medium (100 ng/egg), and high (1,000 ng/egg) of the 2,2 0 ,4,4 0 ,5-pentabromodiphenyl ether (BDE-99) congener along with dimethylsulfoxide (DMSO) control were injected into the yolk sac of un-incubated eggs of zebra finch, Taeniopygia guttata. Offspring development and adult phenotype were followed over three generations. No effects of in ovo PBDE exposure on hatching s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
3
23
1
Order By: Relevance
“…This suggests that these levels were acquired via background contamination or maternal transfer, and may be why we observed higher than expected levels of BDE-47 in all dose groups. Similar background levels were also observed in the eggs and chicks of zebra finches by Winter et al (2013) under the same experimental conditions. Projected cumulative input of BDE-47 was expected to be approximately 0, 105, 1,050, 10,500 ng/g, based on a 20 day dosing regime; however, we observed 515, 516, 1,987, 23,223 ng/g in adipose tissues.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This suggests that these levels were acquired via background contamination or maternal transfer, and may be why we observed higher than expected levels of BDE-47 in all dose groups. Similar background levels were also observed in the eggs and chicks of zebra finches by Winter et al (2013) under the same experimental conditions. Projected cumulative input of BDE-47 was expected to be approximately 0, 105, 1,050, 10,500 ng/g, based on a 20 day dosing regime; however, we observed 515, 516, 1,987, 23,223 ng/g in adipose tissues.…”
Section: Resultssupporting
confidence: 67%
“…Growth hormones, insulin-like growth factors, T4 and T3 are the main hormones responsible for growth in birds post hatch, and it has been suggested that PBDEs can directly impact thyroid hormones through competitively binding with thyroid transport proteins. No effects on growth were observed in the present study, and previous research in our laboratory had shown that a similar compound, BDE-99, also had no effect on thyroid hormone homeostasis or growth in zebra finch offspring (Winter et al 2013;Eng et al 2013). Furthermore, while Fernie et al (2006) did report some marginal effects on growth in kestrels dosed with a mixture of PBDEs, including BDE-99, Winter et al (2013), Eng et al (2013) did not in zebra finches, suggesting interspecies variation in sensitivity to PBDEs as reported by McKernan et al 2009.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…This protocol opens the way for a plethora of cellular-molecular assays that will allow investigators to determine the developmental origins of adult phenotypes. For example, it will be possible to examine gene expression implicated in vocal learning under various environmental conditions or following pharmacological treatments at the earliest stages of development 28,29,30,31 . Although not demonstrated in this paper, this method potentially allows for other procedures such as radioactive in situ hybridization on zebra finch tissue sections and electroporation/in ovosurgery 32,33,34 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…This may not be entirely true because different avian species are known exhibit different responsiveness to PBDE exposure. (Winter et al, 2013) observed that in ovo PBDE levels as low as 10 ng g -1 PBDE-99 may affect reproduction in small passerines with reduction in clutch size noted as the most important indicator of exposure to PBDEs. (Fernie et al, 2009) were probably the first researchers to demonstrate cause-and-effects of PBDE exposure on avian reproduction.…”
Section: Possible Effects Of Observed Pbde Levels On Birds' Reproductmentioning
confidence: 96%